2011
DOI: 10.4236/ajps.2011.23046
|View full text |Cite
|
Sign up to set email alerts
|

Genotype-by-Environment Interaction and Yield Stability Analysis in Finger Millet (<i>Elucine coracana</i> L. Gaertn) in Ethiopia

Abstract: Finger millet is one of the most neglected and underutilized crops worldwide, yet an important food cereal for millions of poor farmers in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
1

Year Published

2015
2015
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 3 publications
2
17
1
Order By: Relevance
“…Hence, it is mandatory to split the contribution of individual sorghum genotypes to create the total GEI effect. And similar research results have been reported for most crops under Ethiopian conditions as, for example, Muhe and Assefa (2011) for bread wheat [7], Gedif and Yigzaw (2014) for potato [8], Adugna et al (2011) for finger millet [9]. This calls for the use of another model that fits the proper evaluation of the tested genotypes, and several methods are used to analyse GEI [10,11,12].…”
Section: Analysis Of Variancesupporting
confidence: 64%
See 1 more Smart Citation
“…Hence, it is mandatory to split the contribution of individual sorghum genotypes to create the total GEI effect. And similar research results have been reported for most crops under Ethiopian conditions as, for example, Muhe and Assefa (2011) for bread wheat [7], Gedif and Yigzaw (2014) for potato [8], Adugna et al (2011) for finger millet [9]. This calls for the use of another model that fits the proper evaluation of the tested genotypes, and several methods are used to analyse GEI [10,11,12].…”
Section: Analysis Of Variancesupporting
confidence: 64%
“…Finally, genotype V8 (PGRC/E #222880) was registered by the given name "Chare" in 2009. Similarly improved varieties have been released using AMMI model in Ethiopia as, for example, finger millet [9] and bread wheat [7].…”
Section: Biplot Analysismentioning
confidence: 99%
“…The second approach is to find stable genotypes and to use them across a range of environments (FINLAY and WILKINSON, 1963). However, stability per se is not necessarily a positive factor and it is desirable only when associated with high mean yield (ADUGNA et al, 2011). Present study evidenced that Hungarian provenance Valkonya (HU42) showed average stability over tested environments, as well as above average mean height growth.…”
Section: Implication Of Provenance By Site Interaction In Light Of CLmentioning
confidence: 62%
“…Indigenous to the highlands of Uganda and Ethiopia, finger millet is widely produced by small scale landholders and consumed locally (Adugna et al 2011). The crop possesses greater impact on the poor in Africa through the provision of food security and economic growth.…”
Section: Introductionmentioning
confidence: 99%